Immediation I - Manning, Erin; Munster , Anna; Stavning Thomsen, Bodil Marie (Open Humanities Press, 2019)
All "media-tion" stages and distributes real, embodied - that is, immediate, events. The concept of immediation entails that cultural, technical, aesthetic objects, subjects, and events can no longer be abstracted from the ways in which they contribute to and are changed by broader ecologies. Immediation I and II seek to engage the entwined questions of relation, event and ecology from outside already claimed territories, nomenclature and calls to action.